An Analysis of the Scope Variations in Intellectual Capital Disclosure: Perspectives of Indonesian State Universities - Ahmad Juanda; Setu Setyawan; Dwi Irawan; Lia Candra Inata (Universitas Muhammadiyah Yogyakarta, Indonesia, 2021)
Research aims: This study aims to examine and analyze the differences in intellectual capital disclosure between Indonesian state universities.Design/Methodology/Approach: The data comprises all state universities listed in 4ICU (4 International Colleges University) in 2020. To analyze the data, the researchers used content analysis and the independent sample t-test. This study used three indicators (location, number of applicants, and number of study programs) to analyze the differences in intellectual capital disclosure between state universities in Indonesia.Research findings: The study results show scope variation in intellectual capital disclosure based on location and number of applicants. However, based on the number of study programs, no variation was found.Theoretical contribution/Originality: The scope variation in intellectual capital disclosure between Indonesian state universities, especially regarding the indicators such as study programs and locations, is a rare topic of study. It is compelling and requires further study.Practitioner/Policy implication: This study is potentially relevant to academicians, researchers, and stakeholders. By analyzing the scope variation in intellectual capital disclosure between Indonesian state universities using three indicators, this study provides insight on the importance of delivering information about universities to the public to improve credibility and attract more applicants.